Rapid Characterisation of Farming Systems in Africa RISING: Malawi - International Crops Research Institute for the Semi-Arid Tropics; Wageningen University and Research (International Food Policy Research Institute, 2014)
This data study contains data from a household and community survey in support of Africa RISING farming systems analysis. Project title: AfricaRISING-Sustainable Intensification of Maize-Legume-Livestock Integrated Farming Systems in East and Southern Africa Project abstract: Sustainable intensification of mixed crop livestock systems is a key pathway towards better food security, improved livelihoods and a healthy environment. As part of the US government?s Feed the Future initiative to address hunger and food security issues in sub-Saharan Africa, the US Agency for International Development (USAID) is supporting three multi-stakeholder agricultural research projects to sustainably intensify key African farming systems. In East and Southern Africa, the project is being implemented in Tanzania, Malawi, and Zambia. In Tanzania, the project is being implemented in Babati and Kongwa districts in Manyara region of northern Tanzania and Kiteto district in Dodoma region, central Tanzania. The action sites were selected to acknowledge agroecological differences, allow appropriate targeting of technologies and strategies, and complement the development efforts of another USAID-supported program, the Tanzania Staples Value Chain (NAFAKA) project. In Malawi, the project is being implemented in Ntechu and Dedza districts in central Malawi where maize-based productions systems are dominant. Agroecological considerations guided the identification of research action sites. The pilot site for the study will be Eastern and Lusaka Provinces in Zambia. Project website: http://africa-rising.net